Impact of Pharmacist Intervention on Improving Knowledge, Attitude and Practice among Hypothyroid Patients - Yadav, Anita; Gupta, Sunita Kumari; Piryani, Rano Mal (Nepal Mediciti Medical Journal, 2022)
BACKGROUND Hypothyroidism causes considerable morbidity. Lack of awareness can lead to poor disease management. This study aimed to investigate the effect of pharmacist-provided counselling in terms of knowledge, attitude, and practice outcomes in hypothyroid patients. METHODS This was a prospective interventional study conducted in a tertiary care hospital of Nepal from September 2019 to February 2020. Based on the inclusion and exclusion criteria, a total of 94 hypothyroid patients were enrolled in this study. Simple Random sampling technique was used. The study population was divided into a test group and control group. The knowledge, attitude, and practice of patients regarding hypothyroidism were assessed and recorded at baseline using questionnaire and counselling was done. After one-month follow-up patients were again assessed using same questionnaire. Data was analyzed using Statistical Package for the Social Sciences version 25. RESULTS The mean knowledge, attitude, and practice scores before intervention of the test group were 6.16±2.14, 18.90±2.29 and 4.53±1.12 respectively, and these scores were changed to 12.48±1.53, 22.04±0.92 and 6.00±0.00 respectively, after the intervention (p < 0.05). Likewise, the mean knowledge, attitude, and practice scores of the control group at baseline were 8.90 ± 3.69, 18.85 ± 2.01 and 4.71 ± 1.29 respectively, and after one-month follow-up the mean scores were changed to 7.88 ± 0.77, 11.50 ± 1.59 and 4.40 ± 0.76 respectively. CONCLUSION The pharmacist-provided counselling is useful in enhancing the knowledge, attitude, and practice of hypothyroid patients.